Mary Kee's Defense Mechanism In Matthew Parkhill's The Caller Movie (2011): A Psychoanalytic Approach - Aliyah, Aliyah; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S, M.Hum (2013)
The research is proposed to analyze a defense mechanism in a film with the title The Caller with Psychoanalytic Approach. There are two objectives: the first is to analyze the film in term of structural elements, and the second is to analyze the film based on Psychoanalytic Approach. This study is a descriptive qualitative study, using the film of Matthew Paarkhill' The Caller as the object of analysis of the style study. There are two kinds of data sources use in this analyzing, namely primary and secondary. The primary data are the film and script of the film itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The analysis is started by analyzing Mary's id, ego, superego, and then her anxiety. For the last, the writer makes an analysis of Mary's character using defense mechanism. The outcome of the study shows that the film illustrates a defense mechanism of Mary Kee in a hard world in the early twentieth century. She is stolen one. Her experiences with mysterious caller make her different. Finally, the conclusion of this analysis is that the woman who known as a weak creature can be anything and can do anything to protect her self.